Cagaita (Eugenia dysenterica) jams with paste and dough textures: physical, chemical, and antioxidant evaluation: - SILVA, Monik Maryelle Moreira da; ALVES, Vânia Maria; AMORIM, Katiúcia Alves; SILVA, Edson Pablo da; DAMIANI, Clarissa (Food Science and Technology, 2023)
Jams with paste and dough textures were developed from cagaita (Eugenia dysenterica DC), in which the physicochemical parameters, proximal analysis, and antioxidant activity during storage were characterized. The jams were stored, and the analyses were carried out every 2 months so that possible variations during 8-month storage time were observed. The values were significant (p < 0.05) for most of the variables studied when comparing the two products concerning time. The main variations were humidity, pH, and total titratable acidity. The storage and conditioning of the products influenced the proximal and antioxidant composition values. The production, commercialization, and consumption of cagaita jams are recommended to contribute to income generation and improvement of nutritional support, especially for individuals living in the Cerrado region.